Terpenic fraction of Pterodon pubescens inhibits nuclear factor kappa B and extracellular signal-regulated protein Kinase 1/2 activation and deregulates gene expression in leukemia cells - Pereira Monica Farah; Martino Thiago; Dalmau Sergio Ranto; Paes Márcia Cristina; Barja-Fidalgo Christina; Albano Rodolpho Mattos; Coelho Marsen Garcia Pinto; Sabino Kátia Costa de Carvalho (BMC, 2012)
Abstract Background Plant derived compounds have been shown to be important sources of several anti-cancer agents. As cell cycle deregulation and tumor growth are intimately linked, the discovery of new substances targeting events in this biochemical pathway would be of great value. The anti-leukemic effect of an ethanolic extract of Pterodon pubescens seeds (EEPp) has been previously demonstrated and now we show that a terpenic subfraction (SF5) of EEPp containing farnesol, geranylgeraniol and vouacapan derivatives induces apoptosis in the human chronic myelogenous leukemia cell line K562. This work addresses SF5's antiproliferative mechanisms in these cells since they are still unclear. Methods DNA synthesis in K562 cells was assessed by [3H]-methyl-thymidine incorporation and cell cycle status by flow cytometry. The expression of cyclins D1 and E2, of the cell cycle inhibitor p21 and of the proto-oncogene c-myc was evaluated by semi-quantitative RT-PCR. Extracellular-signal-regulated kinases (ERK) 1/2 and nuclear factor kappa B (NF-κB) activation was evaluated by western blotting. Results In K562 cells, SF5 treatment induced a higher inhibition of DNA synthesis and cell growth than the original EEPp hexanic fraction from which SF5 originated, and also arrested the cell cycle in G1. Exposure of these cells to SF5 led to a decrease in cyclin E2 and c-myc expression while p21 mRNA levels were increased. Furthermore, SF5 inhibited the activation of mitogen-activated protein kinase (MAPK) ERK 1/2 and NF-κB. Conclusions This work suggests that the anti-leukemic action of SF5 is linked to the inhibition of ERKs, NF-κB and c-myc signaling pathways resulting in reduced cyclin E2 mRNA expression and cell cycle arrest in the G1 phase.